Approximate Analytical Expression of Diffusive Lotka-Volterra Prey-Predator Equations via Variational Iteration Method - Govindaraj, Suganya; Rathinam, Senthamarai (Journal of Applied Nonlinear Dynamics, 2026)
The diffusive Lotka-Volterra model of a prey and predator interaction is analyzed. The model is based on nonlinear differential equation with reaction diffusion term. The approximate analytical expression for diffusive Lotka-Volterra differential equation model has been derived. We employ the Variational Iteration Method to solve this nonlinear boundary value problem. Numerical simulation is obtained through MATLAB software. Both the analytical results and numerical simulation are compared and there is a satisfactory agreement between them.